2014
DOI: 10.1038/npjpcrm.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the provision of smoking cessation assistance: a qualitative study among Romanian family physicians

Abstract: Background:Smoking cessation is the most effective intervention to prevent and slow down the progression of several respiratory and other diseases and improve patient outcomes. Romania has legislation and a national tobacco control programme in line with the World Health Organization Framework for Tobacco Control. However, few smokers are advised to quit by their family physicians (FPs).Aim:To identify and explore the perceived barriers that prevent Romanian FPs from engaging in smoking cessation with patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…A recent study reported five main barriers to smoking interventions by PCPhs: limited perceived role for PCPhs, lack of time during consultations, past experience and presence of disincentives, patients’ inability to afford medications, and lack of training in smoking cessation skills [ 29 ]. In a previous study, the majority of PCPhs felt that smoking cessation support was too time consuming [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported five main barriers to smoking interventions by PCPhs: limited perceived role for PCPhs, lack of time during consultations, past experience and presence of disincentives, patients’ inability to afford medications, and lack of training in smoking cessation skills [ 29 ]. In a previous study, the majority of PCPhs felt that smoking cessation support was too time consuming [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This diversity is contingent on several factors, among which are the smoking behavior of the GPs, their attitudes towards smoking, reservations regarding inducing anxiety or guilt among pregnant women, but also self-confidence in providing cessation support 23 . A qualitative study involving family physicians (general practitioners) in Romania suggested that they generally feel untrained to offer smoking cessation support, emphasizing the need to integrate appropriate training in their professional development 24 . More research should be conducted to assess the capacity of the healthcare system to effectively offer support to pregnant women in their cessation attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives on academic detailing or educational outreach carried out in developed countries 10 , 11 , 26 may not relate to the health service context in low- and middle-income countries. Implementation in countries (such as Brazil) where family medicine is an emerging speciality has specific challenges, as established hierarchies are challenged 27 and the boundaries shift between new professional roles. The WHO’s Package of Essential Non-Communicable Disease Interventions 28 advocates collaborative integrated care to improve case detection, diagnosis and management of respiratory disease, but there are a few implementation studies in low- and middle-income countries testing educational strategies to improve capacity and quality of care.…”
Section: Discussionmentioning
confidence: 99%